(Mythologies of) diving, flying and in-between. Issue 3 (2nd September 2018) - Wilson, Louise K
ABSTRACT: This paper builds on the half-remembered reading of an interview with artist and deep-sea diver Ian Munroe to discuss how artists intervene into scientific research laboratories and other unusual environments. In the process, these embodied practices can be argued to evoke Baradian 'intra-actions' in being productive of situated forms of knowing that question the separation of the subject and object of enquiry.